(3QSGdI aj Gdhabs - (3SMfhf Hf YKeGfs ((3oeUWai Hf jhfS s)
(3ChdgG (B:s
(3GdMeO ddg GdPj hab ef TBA ef YHGOg Edi PcQg s
(3BNQgG (B:s
(3hjMed Ydi QCS GdWGdH Ef cGf GdYed ddNjQ NjQkG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3HZOGO (B(453) s
Keywords: (3GdMQha h GdChaGbs